Synthesis and Characterization of Novel Analogues of Lopinavir - Rajesh Reddy, Peketi; Musunuri, Sivanadh; Ramasekhara Reddy, D.; Subrahmanyam Chittala, V.; Murthy, P.V.N.S.; Krishnamohan, K. (Asian Journal of Chemistry, 2020)
The present work describes the identification, origin, synthesis, characterization and control of four novel analogues of lopinavir viz. leucine analogue of lopinavir, isoleucine analogue of lopinavir, methyl analogue of lopinavir and dihydroxy analogue of lopinavir.